2007
DOI: 10.1097/mpa.0b013e31806da090
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Clinicopathological Features of the Types of Intraductal Papillary-Mucinous Neoplasms of the Pancreas

Abstract: Evaluation of the histological types of IPMN may help to predict the clinical course of patients with IPMN and to design improved clinical management for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 5 publications
1
62
0
Order By: Relevance
“…To our knowledge, this is the first report describing the relationship between invasiveness and TSP1 immunoreactivity in IPMN of the pancreas. Several investigators have reported clinicopathological and biological differences on comparing histologic subtypes of IPMN (5,12,13,17,20,25). Using the TSP1 expression pattern, we also analyzed differences in stromal invasion within histological subtypes of IPMN.…”
Section: References Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first report describing the relationship between invasiveness and TSP1 immunoreactivity in IPMN of the pancreas. Several investigators have reported clinicopathological and biological differences on comparing histologic subtypes of IPMN (5,12,13,17,20,25). Using the TSP1 expression pattern, we also analyzed differences in stromal invasion within histological subtypes of IPMN.…”
Section: References Discussionmentioning
confidence: 99%
“…2 Patients in the strongly positive group, with more than 30% of the cancer stroma positive for TSP1 (---, n = 23), showed a significantly poorer prognosis compared to that of patients in the negative-weakly positive group (-, n = 57; P = 0.008 log-rank test). (9,13,17). However, cases of gastric-type IPMNs tended to show a higher incidence of branch duct-type IPMNs, but there was no significant association between the histological subtype and macroscopic type in our study.…”
Section: Clinicopathological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric and pancreatobiliary subtypes are more often associated with invasive tubular adenocarcinoma versus intestinal subtype, which is frequently associated with invasive colloid carcinoma. [5][6][7][8] Furthermore, studies have reported conflicting evidence on whether the histologic IPMN subtype has prognostic significance. [8][9][10][11][12] The Verona consensus meeting in 2013 recently led to the publication of guidelines for pathologic reporting of IPMN with the recommendation that pathologists provide a histologic subtype.…”
mentioning
confidence: 99%
“…IPMN can be divided according to its anatomical location as main duct -branch duct-and mixed-IPMN. The histological classification divides IPMN into four main categories: gastric, intestinal, pancreatobiliary and oncocytic type [14]. Both classifications are very important in determining the malignant potential of the disease.…”
Section: Pathologymentioning
confidence: 99%